Development of a high-performance pseudocapacitive composite via electroless deposition of silver nanoparticles on micro-sized silicon - Sakshi Juyal; Abhilasha Mishra; Ankur Jain; Kriti Shrivastawa; Aditya Singh; Monika Dumka; Fateh Singh Gill; Mohit Bajaj; Ievgen Zaitsev (Scientific Reports)
Abstract An energy material has been developed using a one-step chemical reduction method, incorporating silver nanoparticles (AgNPs) that encapsulate micro-sized silicon (mSi) flakes. SEM investigation revealed complete encapsulation of silicon flakes by AgNP’s dendritic structure, EDX confirmed the deposition of Ag on Si flakes. Raman spectroscopy confirmed the formation of silver and silicon oxides. In a three-cell configuration, the low equivalent series resistance and charge transfer resistance indicated that Ag served as the conductive channel for charge transfer. The CV curves displayed a 1.7 V voltage window attributed to amorphous SiO2, which offered a significant specific capacitance of 330.6 F g−1 at a scan rate of 5 mV s−1. The pseudocapacitive nature of the developed material, in comparison to other Ag-based composites and pseudocapacitive materials, achieved an energy density of 37.83 Wh kg−1 and a power density of 6374 W kg−1 at a current density of 7.5 A g−1 in a three-cell configuration. The nanostructured Ag combined with mSi is suitable as a renewable charge storage material.